ТHE LEFT IN MACEDONIA: OBSTACLES AND OPPORTUNITIES FOR REVIVAL - Vankovska, Biljana (Politeia, 2025)
This article explores the underexamined issue of left-wing politics in Macedonia, a region often overlooked in broader academic discussions on political transformation in the former Yugoslavia. It addresses key challenges faced by the Left in the post-socialist era, including ideological fragmentation, neoliberal economic policies imposed by the West, and the rise of ethno-nationalist elements in the Macedonian political landscape since 2001. These factors have significantly weakened the influence of leftist ideology in a country marked by ethnic division and largely under Western influence. The article argues that Macedonia's so-called leftist parties, mainly remnants of the former regime, have increasingly adopted neoliberal policies, distancing themselves from traditional socialist values and eroding their connection to the working class. The rise of Levica (The Left), a political party born from a grassroots social movement, offers a potential avenue for revitalizing democratic participation and political transformation in the country. A central focus of the article is the viability of genuine left-wing ideology and policy within the constraints of Macedonia’s NATO and EU orientation. The article concludes that Levica’s future success will hinge on its ability to balance national identity concerns with broader social and economic goals and effectively challenge the entrenched political establishment.
Keywords: Political transition; political participation; leftist ideology; Macedonia; The Left